2012
DOI: 10.5267/j.msl.2012.04.002
|View full text |Cite
|
Sign up to set email alerts
|

A development in balanced scorecard by designing a fuzzy and nonlinear Algorithm (case study: Islamic Azad university of Semnan)

Abstract: The success of each organization depends undoubtedly on the quality of its management and management quality depends on decision quality and information quality on the quality of its measurement and proportion. Therefore, its accuracy and measurement has a key role in the success of the organization and the weakness of performance evaluation and managerial control system can transfer to a barrier for the growth of organization. Performance evaluation systems are now dividable to two traditional group (performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Our recent study on ionic strength dependence of copper complexes based on spectrophotometric measurements in aqueous, organic and surfactant media revealed that it can form a fairly stable complex with Cu 2+ ion. 45 Therefore, we decided to utilize of this reagent as an effective modifier for our studies. Additionally, some preliminary experiments were performed to evaluate the quantitative retention and subsequent clean-up and extraction of copper(II) traces in the absence and presence of PAN by the OSPM disks.…”
Section: Resultsmentioning
confidence: 99%
“…Our recent study on ionic strength dependence of copper complexes based on spectrophotometric measurements in aqueous, organic and surfactant media revealed that it can form a fairly stable complex with Cu 2+ ion. 45 Therefore, we decided to utilize of this reagent as an effective modifier for our studies. Additionally, some preliminary experiments were performed to evaluate the quantitative retention and subsequent clean-up and extraction of copper(II) traces in the absence and presence of PAN by the OSPM disks.…”
Section: Resultsmentioning
confidence: 99%
“…In this model, the entire aspects of an organization are investigated, dominantly. Mozaffari et al (2012) presented an operational trend for the implementation of BSC model based on multiple criteria decision making (MCDM) techniques. They proposed a strategic planning for Islamic Azad university of Semnan and suggested a framework to validate the suggested structure's capacities.…”
Section: Introductionmentioning
confidence: 99%
“…Kaplan and Norton are believed to be the first who introduced the idea of BSC (Kaplan & Norton, 1996, 2000, 2002, 2004. Mozaffari et al (2012) performed a BSC method to measure the performance of a university based organization based on an adaptation of fuzzy numbers for handling the existing uncertainty on the numbers. Danaei and Hosseini (2013) investigated the existing strategic objectives in the strategy map of a pipe company located in city of Shiraz, Iran and designed a questionnaire and distributed it among 31 managers, 94 regular employees and 110 customers of this firm for the fiscal year ended 2011.…”
Section: Introductionmentioning
confidence: 99%